Abstention from Drug Use and Delinquency Increasing among Youth in the United States, 2002–2014. (29th July 2018) - Vaughn, Michael G.; Nelson, Erik J.; Oh, Sehun; Salas-Wright, Christopher P.; DeLisi, Matt; Holzer, Katie J.
ABSTRACT: Background : Trends in abstaining from substance use and delinquency among adolescent's ages 12–17 in the United States was examined. Methods : Data was derived from the National Survey on Drug Use and Health (NSDUH) involving non-Hispanic white, African American, and Hispanic respondents ( n = 98, 620) and spanning the years 2002–2014. Logistic regression was used to examine significance of trend year and correlates of low-risk and high-risk behavioral groups relative to abstaining. Results : Overall, the prevalence of abstaining was 47.56% between 2002 and 2014. Prevalence increased significantly among all adolescents from 44.85% in 2002 to 53.58% in 2014. Relative to abstainers nonabstaining youth were more likely to be male, and report lower household income, poorer grades, depression, and lower levels of parental affirmation and control. Conclusions : Findings indicate that there is a corresponding increase in abstaining mirroring the recent decreases found in adolescent drug use found in national surveys.